Analisis Perbandingan Kadar Nikel (Ni) dan Besi (Fe) pada Lokasi Pengeboran dan Lokasi Penambangan PT. Almharig Mineral Provinsi Sulawesi Tenggara - Jafar, Nurliah; Kadar, Muhammad Ilham; Alrasyid, Vandy Fadli (Jurnal of Mining Insight, 2023)
One of the obstacles in nickel mining is the change in nickel (Ni) and iron (Fe) content from drilling data that does not match the content at the mining location. The study aims to determine the percentage change in nickel (Ni) and iron (Fe) content from drilling data with the mining location. The research method includes processing samples from drilling results and results at the mining location in the laboratory to determine the comparison of content. The next stage is processing and analyzing content data to determine the average nickel and iron content. The results of the identification of drill point data produced an average content of Ni = 1.90% and Fe = 22.86%. While the average content at the mining location is Ni = 1.86% and Fe = 20.55%. Furthermore, the difference in content at the drilling location and at the mining location can be seen, namely Ni = 0.04% and Fe = 2.31%. From the research results, it can be concluded that the levels of identification results at the drilling location have different levels compared to those at the mining location, where the percentage comparison of nickel levels is 0.04% while iron is 2.31%.